On transformations in financing structure in an affluent society - Gunther Tichy (WWWforEurope, 2015)
The savings measures of private households currently exceed the limited financing needs of companies around the world, and the difference is reflected in an increase in sovereign debt. In the EU, over the last two and a half decades non-financial corporations recorded funding surpluses in one out of three years, and in the more affluent EU countries (EU 15) this was even recorded every second year. There is much to indicate that this is not just a result of the financial crisis, but is also globally founded in the Southeast Asian economic model, while in Europe this is a symptom of the affluence of society, as financial security takes on greater significance and slower growth requires fewer investments. Economic policy should therefore be prepared for the current situation to persist; without counter-measures there would have to be a recessive adjustment of savings capacity to the debt preparedness of the economy and state. In these countries, worldwide distortions primarily based in Southeast Asian, exportbased economic policy can only be counter-balanced with a stronger domestic-market-oriented policy and significant appreciation (the task of the dollar peg). Such initiatives exist, but given the scale of the problem, a long transitional phase is to be expected. In the EU, a broad and well-balanced package of measures is required. It would have to dampen austerity through confidence building, in addition to improving corporate finance and reviving severely limited investments in the public sector. Furthermore, particularly in those countries in which the financing and use of sovereign debt do not present a problem, there should be a re-introduction of the previously typical division into a surplus-achieving budget for current expenditures and a budget for investments. This would enable the debt-backed financing of primarily immaterial investments within certain limits.
Keywords: 330; Sozialstaat; Finanzierung der Sozialversicherung; Sparen; Wirtschaftspolitik; EU-Staaten